Calculation of terminal falling velocity of spherical particles moving through polymer solutions using a Power-law viscosity model - Machač, Ivan; Šiška, Bedřich (University of Pardubice, 2019)
The paper deals with the determination of the terminal velocity of solid spherical particles falling slowly in unbounded purely viscous shear-thinning polymer solutions. The relationships are given for calculation of a sphere terminal velocity falling in the creeping flow region using a power-law viscosity model. The comparison is presented for terminal velocities calculated according to the aforementioned relationships with those obtained experimentally by measuring the terminal velocity of spheres in the aqueous solutions of polymers. By considering the shape of the viscosity function of the polymer solutions, it was necessary to use a simple iterative method to estimate the suitable interval of shear rates for determination of the power-law model parameters.
Keywords: sphere free fall; non-Newtonian fluids; creeping flow; power-law model